2010
DOI: 10.1007/s12039-010-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

A solid-polymer-electrolyte direct methanol fuel cell (DMFC) with Pt-Ru nanoparticles supported onto poly(3,4-ethylenedioxythiophene) and polystyrene sulphonic acid polymer composite as anode

Abstract: Nano-sized Pt-Ru supported onto a mixed-conducting polymer composite comprising poly(3,4-ethylenedioxythiophene)-polystyrene sulphonic acid (PEDOT-PSSA) is employed as anode in a solid-polymer-electrolyte direct methanol fuel cell (SPE-DMFC) and its performance compared with the SPE-DMFC employing conventional Vulcan XC-72R carbon supported Pt-Ru anode. Physical characterization of the catalyst is conducted by Fourier-transform infra-red (FTIR) spectroscopy, X-ray diffraction (XRD), Scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
(33 reference statements)
1
5
0
1
Order By: Relevance
“…[167][168][169] In another study, it was found that the Pt-Ru anode nanocatalyst, supported on poly(3,4-ethylenedioxythiophene)-polystyrene sulphonic acid (PEDOT-PSSA) matrix, produced a peak power density of 105 mWcm ¡2 , which was 30% higher than that obtained for the same catalyst on carbon supports. 170 From this and other similar studies, PEDOT-PSSA composite appeared as a promising support material for anode catalysts. A hierarchical N-doped carbon nanotube-graphene hybrid nanostructure (NCNT-GHN), grown in situ inside the inner cavities of the NCNTs, were synthesized by employing a onestep water-assisted chemical vapor deposition (CVD) route.…”
Section: Catalyst Supportssupporting
confidence: 63%
“…[167][168][169] In another study, it was found that the Pt-Ru anode nanocatalyst, supported on poly(3,4-ethylenedioxythiophene)-polystyrene sulphonic acid (PEDOT-PSSA) matrix, produced a peak power density of 105 mWcm ¡2 , which was 30% higher than that obtained for the same catalyst on carbon supports. 170 From this and other similar studies, PEDOT-PSSA composite appeared as a promising support material for anode catalysts. A hierarchical N-doped carbon nanotube-graphene hybrid nanostructure (NCNT-GHN), grown in situ inside the inner cavities of the NCNTs, were synthesized by employing a onestep water-assisted chemical vapor deposition (CVD) route.…”
Section: Catalyst Supportssupporting
confidence: 63%
“…[11][12][13] There are many reports of bimetallic Pt-M catalysts with increased electrocatalytic activity, where M represents a transition metal such as Cr, Mn, Fe, Co, Ni, Cu, Zn [14][15][16][17][18][19][20][21][22][23] or a noble metal such as Ru, Pd, Ag and Au. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Au is a special metal in view of its inertness in bulk state and its high catalytic activity at the nanoscale. This unique property of the nanoscaled Au has been found to show unprecedented electrocatalytic activity for CO oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The higher electronic conductivity of CPs compared to that of the conventional carbon-based catalyst support this higher attention during past two decades. Additionally, the higher surface area and unique synergistic effects with the metal NPs/metal oxide play an important role to improve the electrocatalytic activity of the catalysts and to stabilize fuel cell performance [ 39 , 40 ]. A significant effort has been made in the fabrication of Pt-free catalysts deposited on CPs, although loading of low-Pt nanomaterials on polymers is also used due to their high catalytic performance.…”
Section: Cpnh-based Electrode Materialsmentioning
confidence: 99%